Case driven TLC model checker analysis in energy scenario - Shkarupylo, Vadym; Blinov, Ihor V.; Dusheba, Valentyna; Alsayaydeh, Jamil Abedalrahim Jamil (2023)
Today, model checking techniques and corresponding tools are widely applied in diverse case driven scenarios, the safety critical ones in particular. Addressing current situation in Ukraine, an energy domain is among the topical spheres, where safety critical business processes take place. To foster the functional safety of corresponding program-algorithmic solutions, the model checking techniques and related tools are applied to the formal specifications of named solutions. Doing so is not a trivial task: it depends on a particular use case scenario determining the architecture (structure and couplings) of the resulting design artifact. Moreover, the outcomes of formal techniques and tools application directly depend